Water Use Efficiency of Long Staple Cotton Varieties in Southern Zone of Uzbekistan - Avliyakulov Mirzoolim; Rajabov Nurmamat; Abdullaev Jamshid; Kalandarova Safiya (BIO Web of Conferences, 2023)
Previous research established field capacity (Fc) based irrigation scheduling for upland cotton (Gossypium hirsutum L.) varieties in Uzbekistan. In this paper, the irrigation scheduling Fc for two long staple cotton (Gossypium barbadense L.) varieties and its effect on seed-lint yield and irrigation water use efficiency and water consumption of plants were reported. The field experiments were conducted in the condition of takyr soils with mechanical composition of silt loam in southern zone of Uzbekistan, at the Kashkadarya Experimental Station of Uzbekistan’s Cotton Breeding, Seed Production and Agrotechnologies Research Institute in 2018, 2019 and 2020. In research, cotton growth stages such as germination to flowering, flowering to boll formation, and maturation were considered for the development of irrigation scheduling with respect to field capacity water content (Fc). Irrigation scheduling based on percentages of Fc and mineral fertilizer application rate of N250P175K125 should be considered applicable practices for long staple cotton varieties on silt loam soils of the southern zone of Uzbekistan and for similar soil-climatic conditions of Central Asian countries.